2023
DOI: 10.3389/fimmu.2023.1166052
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of exhausted CD8+ T cell feature as a prognostic model of HCC

Abstract: ObjectivesThe exhausted CD8+T (Tex) cells are a unique cell population of activated T cells that emerges in response to persistent viral infection or tumor antigens. Tex cells showed the characteristics of aging cells, including weakened self-renewal ability, effector function inhibition, sustained high expression of inhibitory receptors including PD-1, TIGIT, TIM-3, and LAG-3, and always accompanied by metabolic and epigenetic reprogramming. Tex cells are getting more and more attention in researching immune-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…And some evidence indicated that CACYBP was involved in regulating TME in tumors, such as hepatocellular carcinoma, esophageal cancer and colorectal cancer [49][50][51] . CACYBP may be a promising target for cancer immunotherapy, especially for hepatocellular carcinoma [52][53][54] . In the present study, we found that CACYBP expression was negatively linked with the ESTIMATEScore, the ImmuneScore, and the StromalScore in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…And some evidence indicated that CACYBP was involved in regulating TME in tumors, such as hepatocellular carcinoma, esophageal cancer and colorectal cancer [49][50][51] . CACYBP may be a promising target for cancer immunotherapy, especially for hepatocellular carcinoma [52][53][54] . In the present study, we found that CACYBP expression was negatively linked with the ESTIMATEScore, the ImmuneScore, and the StromalScore in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Although some scholars have conducted related studies on Tex and HCC, there is still a lack of research on the regulation of Tex transcription factors and HCC. 26 , 27 Transcription factors regulating Tex have been gradually discovered, such as IRF4, BATF, NFATc1, NR4A, TBX21, EOMES and TOX. 28–30 …”
Section: Introductionmentioning
confidence: 99%
“…25 Although some scholars have conducted related studies on Tex and HCC, there is still a lack of research on the regulation of Tex transcription factors and HCC. 26,27 Transcription factors regulating Tex have been gradually discovered, such as IRF4, BATF, NFATc1, NR4A, TBX21, EOMES and TOX. [28][29][30] IRF4 is a T-cell receptor (TCR) signal-sensitive transcription factor that interacts with BATF and NFAT to promote PDCD1 transcription.…”
Section: Introductionmentioning
confidence: 99%